Community Perception of West Coastal District towards Marine Sector Development (Fisheries and Tourism): Process Hierarchy Analysis (AHP) - Feri Hardani; Neli Aida; Toto Gunarto (Budapest International Research and Critics University, 2022)
Pesisir Barat Regency is designated as one of the underdeveloped areas through PP 63 of 2020, based on this, it is necessary to conduct research related to regional development strategies, the West Coast Regency which has a coastline of 210 KM makes this a potential of the region as development capital. Development also requires the role of the community so that these development goals can be achieved, this study looks at how the community's perception of the development of the marine sector (fishery and tourism) is, this study uses the Hierarchical Process Analysis (AHP) method to see how the community's perception is based on the results of research in several main sectors. Based on the community's perception is marine tourism, coastal marine tourism, marine capture fisheries, and marine aquaculture.